Library as Mental Health Center of Bangka Belitung Islands Province - Pasaribu, Waldimer; Rahman, Bustami; Harahap, Fitri Ramdhani; Herdiyanti, Herdiyanti (Universitas Syiah Kuala, 2024)
Mental health is an important part for every individual. Individuals maintain and maintain mental health by implementing a healthy lifestyle. Mental health is an issue that has received global attention because of its significant impact on the quality of life of individuals in the social environment. Mental health encompasses the psychological, emotional, and social aspects of an individual, becoming an important focus in the library environment. Libraries are starting to show their potential as effective and inclusive mental health centers in the Bangka Belitung Islands Provincial Library. In this research, the library has the function of accessing information, health facilities (calm atmosphere), as well as child-friendly programs that support social inclusion. This research aims to explore the role of libraries as social resources that can be widely accessed and the role of librarians as informants and facilitators in providing a supportive environment for visitors, in line with child-friendly social inclusion on mental health with a focus on psychological perspectives, as well as analyzing the implementation of friendly programs children to increase social inclusion. Implementation of child-friendly principles in libraries aims to create an inclusive environment, a comfortable, creative and educational space for children (individuals) to learn, interact and achieve mental well-being. The research method uses in-depth interviews with librarians and users as the main informants, as well as content analysis of existing programs. Research findings show that libraries can create an environment that supports mental health by providing access to information resources, space for reflection and self-exploration, and positive social interactions. Child-friendly programs, such as book discussion groups, expressive arts workshops, and counseling sessions, are consistently identified as effective means of promoting social inclusion and supporting mental well-being. The implication of this research is the importance of collaboration between librarians, psychologists and other stakeholders in designing and implementing programs that strengthen the role of libraries as mental health centers in society.